Copper Sensing in Alkaline Electrolyte Using Anodic Stripping Voltammetry by Means of a Lead Mediator. Issue 12 (5th October 2017) - Duay, Jonathon; Ortiz‐Santiago, Joed E.; Lambert, Timothy N.
Abstract: Anodic stripping voltammetry (ASV) is an analysis technique that permits the selective and quantitative analysis of metal ion species in solution. It is most commonly applied in neutral to acidic electrolyte largely due to inherent metal ion solubility. Bismuth (Bi) is a common film used for ASV due to its good sensitivity, overall stability and insensitivity to O2 . ASV, utilizing a Bi film, along with cadmium (Cd) and lead (Pb) as the plating mediators, has recently been adapted to determine zinc (Zn) concentrations in highly alkaline environments (30 % NaOH or 35 % M KOH). Successful analysis of Zn in alkaline relies on the ability of the hydroxide to form soluble metal anion species, such as Bi(OH)4 − and Zn(OH)4 2− . Here, we look to extend this technique to detect and quantify copper (Cu) ions in these highly basic electrolytes. However, in general, the use of ASV to detect and quantify Cu ion concentrations is notoriously difficult as the Cu stripping peak potential overlays with that of Bi from the common Bi film electrode. Here, an ASV method for determining Cu concentration in alkaline solutions is developed utilizing Pb as a deposition mediator. As such, it was found that when analyzing Cu solutions in the presence of Pb, the stripping voltammetry curves present separate and defined Cu stripping peaks. Different analyzes were made to find the best stripping voltammetry performance conditions. As such, an accumulation time of 5 minutes, an accumulation potential of≤−1.45 V vs. Hg/HgO, and a concentration of 35 wt% KOH were determined to be the conditions that presented the best ASV results. Utilizing these conditions, calibration curves in the presence of 5.0 ppm Pb showed the best linear stripping signal correlation with an r‐squared value of 0.991 and a limit of detection (LOD) of 0.67 ppm. These results give way to evaluating Cu concentrations using ASV in aqueous alkaline solutions. Abstract :